fac-(2-Amidoethyl-kappa C-2(1),O)aquatrichloridotin(IV) 1,4,7,10,13,16-hexaoxacyclooctadecane (2/1) - Wardell, S.M.S.V.; Harrison, W.T.A.; Tiekink, E.R.T.; de Lima, G.M.; Wardell, J.L. (International Union of Crystallography, 2010)
The asymmetric unit of the title compound, [Sn(C3H6NO)Cl-3(H2O)](2)center dot C12H24O6, comprises a six-coordinate tin complex and a 18-crown-6 molecule, the latter disposed about a centre of inversion. The tin atom is coordinated by three Cl atoms, that define a facial arrangement, a chelating C-, O-ligand, and a water molecule. The resulting CCl3O2 donor set defines a distorted octahedral geometry. The tin-bound aqua ligand forms O-H center dot center dot center dot O hydrogen bonds to the centrosymmetric 18-crown-6 molecule, resulting in a tri-molecular aggregate. These assemble into a supramolecular chain along the a axis being connected by N-H center dot center dot center dot O hydrogen bonds.